2008
DOI: 10.1007/s00125-008-1169-7
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase 1 is deleterious to the function and survival of murine pancreatic islets

Abstract: Aims/hypothesis Inhibition of c-jun N-terminal kinase (JNK) favours pancreatic islet function and survival. Since two JNK isoforms are present in the pancreas (JNK1 and JNK2), we addressed their specific roles in experimental islet transplantation. Methods C57BL/6J (wild-type [WT]), Jnk1 (also known as Mapk8)−/− and Jnk2 (also known as Mapk9) −/− mice were used as donor/recipients in a syngeneic islet transplantation model. Islet cell composition, function, viability, production of cytokines and of vascular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Consistent with this, JNK-deficient mice are protected from HFD-induced obesity and IR [75,115]. Furthermore, recent reports substantiate the involvement of JNK in insulin secretion in pancreatic β-cells [116][117][118][119][120][121][122][123]. JNK is involved in the loss of pancreatic β-cells induced by pro-inflammatory cytokines, and jnk1 deficiency or treatment with JNK inhibitors prevents IL-1β-induced apoptosis of islets and insulin-secreting cell lines [116,124,125].…”
Section: Jnk Activation In Obesity and Diabetessupporting
confidence: 56%
“…Consistent with this, JNK-deficient mice are protected from HFD-induced obesity and IR [75,115]. Furthermore, recent reports substantiate the involvement of JNK in insulin secretion in pancreatic β-cells [116][117][118][119][120][121][122][123]. JNK is involved in the loss of pancreatic β-cells induced by pro-inflammatory cytokines, and jnk1 deficiency or treatment with JNK inhibitors prevents IL-1β-induced apoptosis of islets and insulin-secreting cell lines [116,124,125].…”
Section: Jnk Activation In Obesity and Diabetessupporting
confidence: 56%
“…Deficiency of JNK1 but not JNK2 was reported to result in reduced adiposity and steatohepatitis as well as improved insulin sensitivity in mouse models of obesity [29], [45]. While studies in pancreatic islets suggested important roles for both JNK1 and JNK2 in the survival and function of β-cells [32], [47], the precise metabolic action of each JNK isoform is yet to be delineated. We observed that JNK1, instead of JNK2, mediates the glucose-responsive upregulation of ADAR2 expression, providing another example for JNK isoform-selective regulatory action.…”
Section: Discussionmentioning
confidence: 99%
“…Documented studies have implicated the JNK pathway in metabolic dysregulation associated with obesity, insulin resistance, and type 2 diabetes [29], [30]. In pancreatic β-cells, JNK is thought to be involved in suppression of insulin gene expression under oxidative stress [31] and cytokine-induced apoptosis [32]. While the JNK isoforms may possess functional redundancy in mediating cellular adaptation responses to various stress stimuli, it remains poorly understood whether JNK1 or JNK2 is specifically linked to regulation of different cellular aspects of the nutrient-sensing actions in β-cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, JNK1 knockout mice are protected against diabetes mellitus type 2 while JNK2 knockout mice are resistant against hypercholesterolemiainduced endothelial dysfunction. JNK1 can accelerate the death of pancreatic β cells (Varona-Santos et al 2008). These were first studies on cells and mice transfected with inactive scaffolds or substrates, but so far, JNK research still suffers from the lack of inducible JNK knockouts (Harding et al 2001;Suto et al 2004).…”
Section: Strategies To Block Jnk Activitymentioning
confidence: 99%